Personality Characteristics and Oral Health-Related Quality of Life in an Iranian Adult Population - Naimeh Hasheminejad; Hamidreza Hajizamani; Mohammadi Tayebeh Malek; William Murray Thomson (International Journal of Dentistry)
Self-rated oral health and oral health-related quality of life is known to be influenced by various personality characteristics. The aim of this study was to understand how personality characteristics affect oral health-related quality of life ratings in an Iranian adult population. The study included 443 adult participants recruited from a public dental clinic in Kerman, southeast of Iran. The Oral Health Impact Profile-14 questionnaire was used to assess oral health-related quality of life. Personality traits were determined using the 20-item Positive Affectivity Negative Affectivity Scale. Locker’s single-item global self-rating of oral health was used to obtain information on self-rated oral health. Pearson correlation and negative binomial regression were used for data analysis. A higher negative affectivity score was associated with worse oral heath related quality of life, and a higher positive affectivity score was associated with better rating of oral health-related quality of life. On average, individuals who described their oral health as worse scored higher on Oral Health Impact Profile-14. Negative affectivity and positive affectivity influence individuals’ perceptions of their oral health and quality of life. If possible, investigations of oral health-related quality of life measures should also include a brief personality assessment.